Population Status and Ecological Preferences of the Palm Sommieria leucophylla Beccari in Salawati Island - DIDIK WIDYATMOKO (Bogor Agricultural University, Indonesia, 2010)
Population status and ecological preferences of the New Guinean endemic palm Sommieria leucophylla in a lowland forest of the North Salawati Island Nature Reserve were documented at six different habitat types: river bank, hill slope, hill top, intact, disturbed, and converted forests. Population sizes varied spatially and were dominated by seedlings and juveniles, indicating a growing population. Individuals with stem heights of 0-100 cm and stem diameters of 2-3 cm dominated. The stem height class distribution showed a preponderance of individuals in the juvenile stage class and a strong right hand skew typical of populations in which recruitment and mortality were continuous and density dependent, rather than episodic. S. leucopylla preferred specific habitats with river bank and intact forest being the most suitable habitat. Although the palm tolerated hill slopes, the populations were low and even suppressed at hill tops, and seemed to be sensitive to disturbance and changes in water table. Mortality was higher among the early stages but very low in adults. There was little recruitment in disturbed sites and no establishment in converted forests. To conserve the most important remaining populations, it is crucial to protect the most suitable sites in the reserve.